Comunicação comunitária : o uso das novas tecnologias de informação e comunicação como forma de pertencimento e sustentabilidade nas comunidades carentes de Porto Alegre no início do século XXI - Lage, Louise Costa (2005)
The work tries to establish a concept, or, at least, to point the line of direction of that if it understands today for communftarian communication searching to understand the reality of the use of the new technologies of communication enters the devoid population of Porto Alegre, ln the beginning of cêntury XXI, and makes of this use a form of sustentabilidade and belonging. ln intention to search to prove our tiypothesis, we carry through study of case in four communities: two - the Restinga and the Great Village of the- Sailor (Vila Grande dos Marinheiros) -, in Porto Alegre, considered city metropolis; e others two virtual ones, the Net Women of Radio, a radio communitarian established in format dlfferentiated of that one whom we are accustomed to coexist in written literature until the moment, on or for the comment made from some experiences in thi~ direction, in the Rio Grande Do Sul; e the Center of lndependent Media - CMI _ a community of produoers of communitarían communication